2002
DOI: 10.1614/0890-037x(2002)016[0807:dsfwmi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Diclosulam Systems for Weed Management in Peanut (Arachis hypogaea L.)1

Abstract: Field studies were conducted at Lewiston and Rocky Mount, NC, in 1996 and 1997 to evaluate weed control and peanut response to preplant incorporated (PPI) treatments of diclosulam alone and in systems with postemergence (POST) commercial standard herbicides. All plots received ethalfluralin PPI at 840 g ai/ha. In both years, ethalfluralin plus diclosulam PPI at 17 or 26 g ai/ha followed by (fb) acifluorfen plus bentazon POST, paraquat plus bentazon POST, or imazapic POST controlled common lambsquarters, ivylea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Paraquat ϩ bentazon EPOST, either alone or fb chlorimuron provided less than 80% control; however, all other treatments evaluated provided at least 89% control in 2003 (Table 4). In previous research, diclosulam and flumioxazin PRE, chlorimuron, imazapic, pyridate, and 2,4-DB POST controlled ivyleaf morningglory 70 to 100% (Bailey and Wilcut 2002;Bailey et al 1999aBailey et al , 1999bEdenfield et al 2001;Taylor-Lovell et al 2002). No differences were observed between peanut planting patterns for ivyleaf morningglory control (Table 4).…”
Section: Resultsmentioning
confidence: 68%
“…Paraquat ϩ bentazon EPOST, either alone or fb chlorimuron provided less than 80% control; however, all other treatments evaluated provided at least 89% control in 2003 (Table 4). In previous research, diclosulam and flumioxazin PRE, chlorimuron, imazapic, pyridate, and 2,4-DB POST controlled ivyleaf morningglory 70 to 100% (Bailey and Wilcut 2002;Bailey et al 1999aBailey et al , 1999bEdenfield et al 2001;Taylor-Lovell et al 2002). No differences were observed between peanut planting patterns for ivyleaf morningglory control (Table 4).…”
Section: Resultsmentioning
confidence: 68%
“…Diclosulam has been reported to control yellow nutsedge . 80% with rates ranging from 9 to 16 g ai/ha; well below the labeled rate of 27 g/ha (Bailey and Wilcut 2002;Grichar et al 2004;Swann 2000). Grichar et al also reported at least 90% control of eclipta [Eclipta prostrata (L.) L.], pitted morningglory (Ipomoea lacunosa L.), and Texas millet [Urochloa texana (Buckl.)…”
mentioning
confidence: 88%
“…Diclosulam, flumioxazin, and imazapic alone and in mixtures provide residual control of many broadleaf weeds in peanut when applied at the full label rates (Askew et al 1999;Grichar 2002;Main et al 2005;. Research has been conducted using these three herbicides at rates applied below the manufacture's suggested use rate in peanut in an attempt to maintain weed control while reducing cost and the potential for imazapic carryover (Bailey and Wilcut 2002;Baughman et al 2003;Burke et al 2002;Grichar 1997;Swann 2000). Diclosulam has been reported to control yellow nutsedge .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wide range of chemicals has been used for controlling peanut weeds (Bailey and Wilcut, 2002;Burke et al, 2004;Kumar et al, 2003a). Farmers, in certain areas, prefer mechanical means for controlling weeds owing to the plenty of family members.…”
Section: Introductionmentioning
confidence: 99%